Agama Dan Keadaban Publik - Mahrus As'ad (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2012)
Operasionalization of religion in a civilized community life in inter-relationship between religion complex itself on the one hand with the various elements of culture and society in which individuals reside and live on the other. Complexity of the relationship of religion can not be made freely as it should meet the demands of teaching. Elements of local cultural values are prominent, such as live view of the strong regional ethnic, social control and law enforcement are weak, an easy rule is violated, the authority (authorities) that the state continues to decline, to name of a few, is a major barrier to religion in the running his sacred mission to its full potential in society. Culture of civilized life can not be realized in the concrete life just by relying on faith alone, but also need the willingness of all parties, including state officials, to subjugate himself under the control of the values and norms that exist and run it with full sincerity.